Metabolic Current Production by an Oral Biofilm Pathogen Corynebacterium matruchotii - Naradasu, Divya (Molecules, 2020)
The development of a simple and direct assay for quantifying microbial metabolic activity is important for identifying antibiotic drugs. Current production capabilities of environmental bacteria via the process called extracellular electron transport (EET) from the cell interior to the exterior is well investigated in mineral-reducing bacteria and have been used for various energy and environmental applications. Recently, the capability of human pathogens for producing current has been identified in different human niches, which was suggested to be applicable for drug assessment, because the current production of a few strains correlated with metabolic activity. Herein, we report another strain, a highly abundant pathogen in human oral polymicrobial biofilm, Corynebacterium matruchotii, to have the current production capability associated with its metabolic activity. It showed the current production of 50 nA/cm(2) at OD(600) of 0.1 with the working electrode poised at +0.4 V vs. a standard hydrogen electrode in a three-electrode system. The addition of antibiotics that suppress the microbial metabolic activity showed a significant current decrease (>90%), establishing that current production reflected the cellular activity in this pathogen. Further, the metabolic fixation of atomically labeled (13)C (31.68% ± 2.26%) and (15)N (19.69% ± 1.41%) confirmed by high-resolution mass spectrometry indicated that C. matruchotii cells were metabolically active on the electrode surface. The identified electrochemical activity of C. matruchotii shows that this can be a simple and effective test for evaluating the impact of antibacterial compounds, and such a method might be applicable to the polymicrobial oral biofilm on electrode surfaces, given four other oral pathogens have already been shown the current production capability.